Electrodeposited Co-Mn-Sn multicomponent alloy as an efficient electrocatalyst for hydrogen evolution reaction - Chandran, M. Athira; Karumuthil, Subash Cherumannil; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (International Journal of Hydrogen Energy, 2024)
Despite having exciting material characteristics, the potential of multi-component alloys (MCAs) as electrocatalysts has not been fully realized. In this work, efficient binary and ternary MCA electrocatalysts containing inexpensive metals like Co, Mn and Sn have been prepared via the electrodeposition process. When tested for hydrogen evolution reaction (HER) in an alkaline medium, ternary Co-Mn-Sn alloy displayed enhanced activity with the lowest overpotential of 136 mV, a Tafel slope of 111 mV dec 1 and a very low charge transfer resistance, making it superior to the binary alloys (Co-Mn and Co-Sn), or the single metal catalysts (Co, Mn and Sn). The ternary alloy also displayed high electro-chemical and structural stability, making it a viable electrocatalyst for the hydrogen economy.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Clean energy; electrocatalysis; Electrodeposition; hydrogen evolution reaction; Multi-component alloy; Non-platinum group metals

Establishing a new efficiency descriptor for methanol oxidation reaction and its validation with commercially available Pt-based catalysts - Deshpande, Pooja S.; Radhakrishnan, Thulasi; Prasad, Bhagavatula L. V. (Fuel Cells, 2024)
Direct methanol fuel cells (DMFCs) have received a lot of attention in recent years as promising technology for generating clean and efficient energy. In DMFC, the anode catalyst is a vital component because it is involved in the oxidation of methanol, which produces electrons that can be used as an energy source. Cyclic voltammetry (CV) is commonly used to test the characteristics of the electrode materials before they are employed in the actual fuel cell. Interestingly in the case of DMFCs CV also is a useful technique to obtain vital information about the performance and expected efficiency of the electrodes. In general, the CV of methanol electrooxidation for Pt-based catalysts has two peaks, If in the forward scan (anodic scan) and Ib in the backward scan (cathodic scan). The ratio of these two peaks (If/Ib) is the most commonly used criterion for investigating CO poisoning in catalysts. However, there is a great deal of ambiguity surrounding this criterion, owing to the genesis of Ib. Addressing this we present here a new criterion to evaluate the efficiency of the catalyst using the same CV technique. We validate this newly proposed criterion with commercial Pt/C (comm. Pt/C) and other commercially available alloy catalysts.
Keywords: catalyst poisoning; CO tolerance; direct methanol fuel cells; electrocatalysis; Methanol oxidation reaction

An effective alliance for successful coupling: electrochemical alcohol oxidation mediated conversion of indoles to bis(indolyl)methanes - Baravkar, Mayur D.; Prasad, Bhagavatula L. V. (Journal of Applied Electrochemistry, 2025)
Electro-organic transformation of indoles to bis(indolyl)methanes (BIMs) has been successfully achieved by combining the electrochemical alcohol oxidation reaction (AOR) with indole coupling. The fact that it is the readily available alcohols and not the traditionally used aldehydes or ketones that provide the bridging -CH2- (methylene) for this transformation makes this path extremely attractive and valuable. The formation of aldehydes as reactive intermediates during the AOR has been dexterously utilized to achieve this transformation. Most gratifyingly, the transformation also can be carried out in water-alcohol mixtures and the yields and conversions are better than the most of the previously reported chemical catalytic transformations using specially designed metal complexes. Various substituted indoles were selectively converted to their corresponding BIMs in decent yields. This strategy could further be exploited for the synthesis of different natural products, including the much sought after deuterium substituted ones (as CD3OD is readily accessible), and other important biologically active alkaloids and drug molecules, etc.
Keywords: Alcohol oxidation reaction; Bis(indolyl)methanes; Direct alcohol fuel cell; Electroorganic transformations; Vibrindole A